The subcutaneous defibrillator in patients with low BMI - insights from a large European multicenter registry. (19th May 2022) - Vogler, J; Gasperetti, A; Schiavone, M; Breitenstein, A; Laredo, M; Palmisano, P; Mitacchione, G; Hakmi, S; Ricciardi, D; Arosio, R; Casella, M; Kuschyk, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The subcutaneous implantable cardioverter defibrillator (S-ICD) has become an alternative to transvenous ICDs (tv-ICD), especially in young patients without a need for pacing. One of the current limitations of the S-ICD is the relatively large size of the generator compared to tv-ICDs. There is little evidence whether the size of the current S-ICD generator is associated with an elevated risk of device-related complications in patients with a low body mass index (BMI). Purpose: To compare the device-related complications and long-term outcomes in a large real world cohort of S-ICD recipients in patients with a BMI <18 kg/m2 compared to patients with a BMI >18 kg/m2. Methods: The iSuSI registry is a European, multi-center, open-label, independent, and physician-initiated observational registry. A total of twenty-two Public and Private Healthcare Institutions from 4 different countries in Europe were involved in the registry. All consecutive patients meeting current guideline indications for ICD implantation and undergoing implantation of a S-ICD device (Boston Scientific, Marlborough, Massachusetts, USA) at 21 European institutions enrolled in the registry were used for the current analysis. Patients were classified into two cohorts, depending on the BMI at the time of device implantations: BMI < 18 kg/m2 versus > 18 kg/m2. Results: Out of a total of 1497 pts, 58 pts (3.9%) had a BMI < 18 kg/m2. Patients with BMI <18 kg/m2 were younger (44.6±2.4 vs 50.8±0.4; p=0.004) and more frequently female (58.6% vs 22.3%, p<0.001). No differences in any of the other baseline characteristic were observed. Implantation techniques resulted comparable between the groups (Rates of 2-incision technique: 87.8% vs 91.9%; p=0.256; inter-muscular placement: 89.7% vs 83.3%; p=0.198). Of note, the mean PRAETORIAN score at implantation of patients with BMI <18 kg/m2 was significantly lower (33.8±9.1 vs 54.1±47.3; p=0.035), although the vast majority of pts in both cohorts qualify as at low risk of conversion failure (100% vs 91.4%; p=0.436). Over a median follow up time of 22.4 [11.6–36.8] months, both overall device-related complications (5.2% vs 7.4%) and rates of inappropriate shocks (12.0% vs 8.8%) resulted comparable between the two groups (p =0.517 and p=0.385, respectively). Figure1 reports Kaplan-Meier curves reporting the combined incidence of device-related complications and inappropriate shocks in the two groups (log-rank p = 0.576). Conclusion: No difference in device-related complications and long-term outcomes after S-ICD implantation were observed in patients with BMI <18 kg/m2 compared to the remaining recipients from a large, multi-centered S-ICD registry. Figure 1: Kaplan-Meier-survival curve for the combined endpoint of inappropriate shocks (IAS) and device-related complications (DRC)